Albert Jack's ten-minute mysteries : the world's secrets explained, from the real Loch Ness monster to who killed Marilyn Monroe /: the world's secrets explained, from the real Loch Ness monster to who killed Marilyn Monroe. (2007) - Unknown
No abstract available